Partial differential equations and applications collected papers in honor of Carlo Pucci - Pucci, Carlo; Marcellini, Paolo; Talenti, G. (Giorgio); Vesentini, Edoardo (Lecture notes in pure and applied mathematics, 1996)
Written as a tribute to the mathematician Carlo Pucci on the occasion of his 70th birthday, this is a collection of authoritative contributions from over 45 internationally acclaimed experts in the field of partial differential equations. Papers discuss a variety of topics such as problems where a partial differential equation is coupled with unfavourable boundary or initial conditions, and boundary value problems for partial differential equations of elliptic type.